Comparative Immigrant Education Policies and Practices - Bakır, Kemal Faruk; Akcan, Leyla; Şahin, Birgül; Sluga, Guldane; Odabaş, Ceyda; Kahramanoğlu, Recep; Kuloğlu, Muhammet Esad; Alev, Sedat; Rengi, Öznur; Paçaman, Recep; Arslankara, Veysel Bilal; Çetin, Yavuz; et al. (Sakarya Üniversitesi Yayınları, 2025)
Immigration, as old as humanity itself, continues to reshape societies across the globe socially, economically, and culturally. Among its many dimensions, education stands as one of the most vital and challenging arenas where integration takes form. Comparative Immigrant Education Policies and Practices examines how education systems across different countries respond to the needs of immigrant students, exploring both Türkiye’s experiences and international approaches through a comparative lens. Bringing together theoretical, historical, and practical perspectives, this book offers a comprehensive and multidimensional analysis of immigrant education policies. Each chapter provides an in-depth look at how nations manage educational access, inclusion, and equity for immigrant learners highlighting their successes, shortcomings, and lessons learned. Drawing from global literature, recent research, official reports, and statistical data, this volume serves as an essential reference for scholars, educators, policymakers, and anyone committed to fostering inclusive and democratic education systems in an age of migration.